Neural Coding and Decoding with Spike Times (Spike Timing, 2013)
Examples ... 43 2.4 Tempotron Performance in Latency Code ... 452.4.1 Statistics of Postsynaptic Potential ...46 2.4.2 Capacity ...48 2.4.3 Geometry of the Solution Space ...48